Spatial Inequalities in Long-Run : Perspectives of Economic History and Historical National Accounts - Klein, Alexander; Dyba, Karel, 1940-2024; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This work enhances economists’ understanding of the sources of spatial inequalitiesand the factors determining their changes over time. Research focusing on the temporaldimension of spatial inequalities established that even though they change over time, thatprocess is rather slow. The fact that it takes a long time for geographical distribution ofeconomic activities to change has a profound implication for empirical research: it must take a long-run view to understand the causes of spatial inequalities and their changes over time.Research to date has focus predominantly on a short-run horizon, failing thus to properlycapture the dynamism of spatial inequalities. Time has come to remedy this and provide a comprehensive analysis of the nature, sources, and changes of spatial inequalities over longperiod of time. The spatial inequalities in the United States over 120 year is a uniqueopportunity to do so. Specifically, the case of manufacturing sector and the manufacturingbelt is an excellent example: it emerged around 1860s-1870s, reached its peak in the 1950s and began to dissolute in the 1970s. Hence, by the time the manufacturing belt turned into therust belt, more one hundred years had passed. Therefore, this works deepens our understanding thenature and changes of spatial inequalities by studying the long-run evolution of spatialinequalities in manufacturing in the United States over the period of 120 years.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet